Graft healing after anterior cruciate ligament reconstruction (ACLR) - Shiyi Yao; Bruma Sai-Chuen Fu; Patrick Shu-Hang Yung (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2021)
Anterior cruciate ligament reconstruction (ACLR) is a commonly performed procedure in Orthopaedic sports medicine. With advances in surgical techniques providing better positioning and fixation of the graft, subsequent graft failure to certain extent should be accounted by poor graft healing. Although different biological modulations for enhancement of graft healing have been tried in different clinical and animal studies, complete graft incorporation into bone tunnels and the “ligamentization” of the intra-articular part have not been fully achieved yet. Based on the understanding of graft healing process and its failure mechanism, the purpose of this review is to combine both the known basic science & clinical evidence, to provide a much clearer picture of the obstacle encountered in graft healing, so as to facilitate researchers on subsequent work on the enhancement of ACL graft healing.